2018
DOI: 10.1101/266908
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Network analysis of ChIP-seq data by VULCAN identifies GRHL2 as a key co-regulator of ERa in luminal breast cancer

Abstract: Background Estrogen Receptor-alpha (ER) is the main driver of~75% of all breast cancers.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…GRHL2 occupancy was also found to increase upon E2 treatment at these overlapping sites but not at GRHL2 sites devoid of pS118-ER. This finding is supported by a recent preprint by Holding et al, which reported a genomewide increase of GRHL2 binding in the presence of E2 and many of the E2-induced GRHL2 occupancy sites overlapped ER occupancy sites (76). GRHL2 is a transcription factor involved in embryonic development, and it has been implicated as both a tumor suppressor and an oncogene depending on the cellular context (77,78).…”
Section: Discussionmentioning
confidence: 55%
“…GRHL2 occupancy was also found to increase upon E2 treatment at these overlapping sites but not at GRHL2 sites devoid of pS118-ER. This finding is supported by a recent preprint by Holding et al, which reported a genomewide increase of GRHL2 binding in the presence of E2 and many of the E2-induced GRHL2 occupancy sites overlapped ER occupancy sites (76). GRHL2 is a transcription factor involved in embryonic development, and it has been implicated as both a tumor suppressor and an oncogene depending on the cellular context (77,78).…”
Section: Discussionmentioning
confidence: 55%
“…In trying to make sense of the data we had, we tested alternative methods to integrate it and to increase the power of our genome‐wide experiments, none of which conclusively reproduced the reported cycling. These attempts were not without some success: one of the methods would go on to be published separately . However, none of these ideas definitively confirmed the cycling result we were looking for.…”
Section: Squinting At Datamentioning
confidence: 95%